ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA FINANCIAL STATEMENT FRAUD DENGAN PERSPEKTIF FRAUD DIAMOND (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di JII Tahun 2019-2021) - SHERLY; YOUDHI PRAYOGO; LAILY IFAZAH (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Financial statement fraud refers to the deliberate efforts by an organization to deceive or mislead readers of published financial information, particularly creditors and investors, by presenting materially incorrect or misleading financial reports. This research aims to identify the potential for financial statement fraud using the fraud diamond theory. The fraud diamond comprises four elements of fraud risk developed from the fraud triangle theory. This research is quantitative in nature, and it relies on secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id), industry websites, and the Indonesia Capital Market Directory (ICMD). The population of this study consists of companies listed on the Jakarta Islamic Index (JII) from 2019 to 2021. The sample selection is based on purposive sampling techniques. The results of this research indicate that financial targets affect financial statement fraud, ineffective monitoring influences financial statement fraud, changes in auditors impact financial statement fraud, changes in directors affect financial statement fraud. Furthermore, the F-test results show that the F statistic value of 0.55 is smaller than the F-table value (2.48), which leads to the conclusion that there is a significant relationship among the tested variables.